Recombinant complement receptor 2 radiolabeled with [99mTc(CO)3]+: a potential new radiopharmaceutical for imaging activated complement. - Adam Badar; Sarah DeFreitas; James M McDonnell; Norhakim Yahya; David Thakor; Reza Razavi; Richard Smith; Steven Sacks; Gregory E D Mullen (PLoS ONE)
We describe the design and synthesis of a new Tc-99m labeled bioconjugate for imaging activated complement, based on Short Consensus Repeats 1 and 2 of Complement Receptor 2 (CR2), the binding domain for C3d. To avoid non specific modification of CR2 and the potential for modifying lysine residues critical to the CR2/C3d contact surface, we engineered a new protein, recombinant CR2 (rCR2), to include the C-terminal sequence VFPLECHHHHHH, a hexahistidine tag (for site-specific radiolabeling with [(99m)Tc(CO)(3)(OH(2))(3)](+)). The protein was characterized by N-terminal sequencing, SDS-PAGE and size exclusion chromatography. To test the function of the recombinant CR2, binding to C3d was confirmed by enzyme-linked immunosorbent assay (ELISA). The function was further confirmed by binding of rCR2 to C3d(+) red blood cells (RBC) which were generated by deposition of human or rat C3d and analyzed by fluorescence microscopy and flow cytometry. The affinity of rCR2 for C3d(+), in presence of 150 mM NaCl, was measured using surface plasma resonance giving rise to a K(D)≈500 nM. Radiolabeling of rCR2 or an inactive mutant of rCR2 (K41E CR2) or an unrelated protein of a similar size (C2A) with [(99m)Tc(CO)(3)(OH(2))(3)](+) at gave radiochemical yields >95%. Site-specifically radiolabeled rCR2 bound to C3d to C3d(+) RBC. Binding of radiolabeled rCR2 to C3d was inhibited by anti-C3d and the radiolabeled inactive mutant K41E CR2 and C2A did not bind to C3d(+) RBCs. We conclude that rCR2-Tc(99m) has excellent radiolabeling, stability and C3d binding characteristics and warrants in vivo evaluation as an activated complement imaging agent.